Usia Ibu Dan Paritas Dengan Kejadian Persalinan Prematur - Marcella, Fanna; Anggraini, Anggraini; Isnaini, Nurul; Utami, Vida Wira (Universitas Malahayati Bandar Lampung, 2022)
Background: Preterm labor is the main cause of high perinatal mortality. Globally, prematur events range from 10% to 30%. Data in Indonesia in 2018 states that the number of preterm births in Indonesia reaches 29.5%. Whereas in Lampung Province in 2018 there were 24.8%. Data in Dr. H. Abdul Moeloek Lampung Province, in 2018, there were 124 cases of preterm labor (8.7%) from 1,414 deliveries and increased in 2019, to 141 cases of preterm labor (9.8%) from 1,425 deliveries.Purpose: This research is to find the correation between age and parity to preterm labor in Abdul Moeloek Bandar Lampung Hospital in 2019.Methods: This type of research is quantitative. Analytical survey design with cross sectional time approach. The population in this study was maternity in the Dr. H. Abdul Moeloek Bandar Lampung in 2019, with 1,425 deliveries with a total sample of 126 people, when the research was conducted on March 4, 2020 to April 4, 2020, and the sampling technique used was simple random sampling. Statistical test using the chi-square test.Results: Univariate analysis obtained by the incidence of preterm labor as many as 42 people (33.3%). Most respondents had no-risk age, which was 88 people (69.8%), and risk parity, which was 64 people (50.8%). Bivariate analysis obtained a relationship between age (p-value = 0.005, and OR = 3.333) and parity (p-value = 0.000, and OR = 6.269), with prematur events.For this reason, it is necessary to improve health education for women of childbearing age regarding the impact of preterm labor and the importance of performing complete antenatal care.Conslusion: There is a relationship between age and preterm delivery at H. Abdul Moeloek Hospital, Lampung Province in 2019 (p-value = 0.005, and OR = 3.333) and there is a relationship between parity and preterm delivery at H. Abdul Moeloek Hospital, Lampung Province in 2019 (p- value = 0,000, and OR = 6,269).Suggestion Pregnant women can find information about preterm labor and the factors that influence it, including age and parity by reading books, attending health education, taking regular classes for pregnant women, or by providing information using the Checklist so that pregnant women will be motivated to reduce risk of preterm labor by limiting delivery to ages that are not at risk and also not delivering at high parity. Keywords: Age,Parity,Prematur ABSTRAK Latar Belakang: Persalinan prematur menjadi penyebab utama tingginya angka kematian perinatal. Secara global angka kejadian prematur berkisar antara 10% s.d 30%. Data di Indonesia tahun 2018 menyebutkan bahwa angka kejadian kelahiran preterm di Indonesia mencapai 29,5%. Sedangkan di Provinsi Lampung tahun 2018 sebanyak 24,8%. Data di RSUD Dr. H. Abdul Moeloek Provinsi Lampung, pada tahun 2018, terdapat 124 kasus persalinan prematur (8,7%) dari 1.414 persalinan dan meningkat pada tahun 2019, menjadi 141 kasus persalinan prematur (9,8%) dari 1.425 persalinan.Tujuan: Diketahui hubungan antara usia dan paritas terhadap persalinan prematur di RSUD Abdul Moeloek Bandar Lampung Tahun 2019.Metode: Jenis penelitian ini adalah kuantitatif. Rancangan survey analitik dengan pendekatan waktu adalah cross sectional. Populasi dalam penelitian ini adalah ibu bersalin di Rumah Sakit Dr. H. Abdul Moeloek Bandar Lampung pada tahun 2019, dengan jumlah 1.425 persalinan dengan jumlah sampel sebanyak 126 orang, waktu penelitian dilaksanakan pada tanggal 04 Maret 2020 sampai dengan 04 April 2020, dan teknik sampling yang digunakan yaitu simple random sampling. Uji stastistik menggunakan uji chi-square.Hasil: Analisis univariat diperoleh distribusi frekuensi pesalinan prematur sebanyak 42 orang (33,3%), Sebagian besar responden memiliki usia tidak beresiko, yaitu 88 orang (69,8%), Paritas beresiko, yaitu sebanyak 64 orang (50,8%). Analisa bivariat diperoleh hubungan usia (p-value 0,005, dan OR=3,333) dan paritas (p-value 0,000 dan OR=6,269), dengan kejadian prematur.Kesimpulan: Ada hubungan antara usia dengan persalinan prematur di RSUD H. Abdul Moeloek Provinsi Lampung Tahun 2019 (p-value = 0,005, dan OR=3,333) dan ada hubungan antara paritas dengan persalinan prematur di RSUD H. Abdul Moeloek Provinsi Lampung Tahun 2019 (p-value = 0,000, dan OR=6,269).Saran ibu hamil dapat mencari informasi tentang persalinan prematur dan faktor yang mempengaruhinya termasuk usia dan paritas dengan cara membaca buku-buku, mengikuti penyuluhan kesehatan, ikut dalam kelas ibu hamil secara rutin, atau dengan memberikan informasi dengan menggunakan Daftar Tilik sehingga ibu hamil akan termotivasi untuk mengurangi risiko persalinan prematur dengan membatasi melahirkan pada usia yang tidak berisiko dan juga tidak melahirkan pada paritas yang tinggi. Kata Kunci: Usia, Paritas, Prematur